Reduction in incidence of invasive fungal infection in patients receiving allogeneic stem cell transplantation using combined diagnostic‐driven approach and itraconazole oral solution. Issue 12 (2nd October 2015) - Tzadok, Roie; Shapira, Michael Y.; Moses, Allon E.; Or, Reuven; Block, Colin; Strahilevitz, Jacob
Summary: Invasive fungal infections are an important cause of morbidity and mortality after allogeneic haematopoietic stem cell transplantation. We evaluated, in our allogeneic stem cell transplant patients, the effect on the incidence of invasive fungal infection during neutropenia of a strategy combining a diagnostic‐driven approach with chemoprophylaxis during higher risk periods of graft vs. host disease and prolonged neutropenia, using itraconazole oral solution with parenteral voriconazole bridging. One hundred and thirty patients admitted for allogeneic stem cell transplantation within two predefined 20 month periods were included in the study. Data for all patients were collected prospectively. Implementation of the protocol resulted in the administration of more prophylactic antifungals to more patients. Following implementation, there was a non‐significant decrease in the overall number of invasive fungal infections (IFI) [11 of 65 patients (17.2%) vs. 4 of 65 patients (6.2%, P = 0.051)], as well as in the occurrence of invasive mould infections [8 of 65 patients (12.5%) vs. 2 of 65 patients (3.1%, P = 0.054)]. Survival rates at three and 6 months were not significantly affected. A combined diagnostic‐driven approach and antifungal prophylaxis with oral itraconazole and an intravenous voriconazole bridging protocol, was associated with a reduced, albeit non‐statistically significant, number of IFI in our medical centre.